THE WORD AS A SYMBOLIC BORDER - Paniagua Arguedas, Laura (2006)
The article explores some kinds of hostility that Nicaraguan people face inCosta Rica in their everyday life. In this work it is mentioned that symbolicboundaries are invisible limits, for example: jokes, insults, aggressive words,graphite, etcetera. This article analyse the graphite like symbolic boundarythat presents some ideas of Costa Rican national identity. To finish, is statedthat it is very important to debate about the consequences of our myths ofidentity and national problems.